Stimulating effect of a low-molecular fraction from cord blood on the energy metabolism in leukocytes - Gulevsky, O.K.; Akhatova, Yu. S.; Sysoev А.А.; Sysoeva, I.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The ATP, ADP, and AMP contents are determined in leukoconcentrate cells after incubation in a medium containing a low-molecular fraction (below 5 kDa) from cord blood (0.15 mg/mL) by chemiluminescent analysis. It is shown that the fraction significantly stimulates the accumulation of intracellular ATP and ADP and has no effect on the AMP content. The stimulatory effect of the low-molecular fraction from cord blood is blocked by a glycolysis inhibitor, iodoacetate Na, and a glucose transport inhibitor, cytochalasin B. It is found that the fraction from cord blood enhances the total adenylate pool of leukocytes. It is established experimentally that the presence of the low-molecular fraction from cattle cord blood stimulates the glucose accumulation in leukoconcentrate cells.